Enhanced Recovery Programs in an Ambulatory Surgical Oncology Center. (15th November 2021) - Afonso, Anoushka M.; McCormick, Patrick J.; Assel, Melissa J.; Rieth, Elizabeth; Barnett, Kara; Tokita, Hanae K.; Masson, Geema; Laudone, Vincent; Simon, Brett A.; Twersky, Rebecca S.
Abstract : BACKGROUND: We describe the implementation of enhanced recovery after surgery (ERAS) programs designed to minimize postoperative nausea and vomiting (PONV) and pain and reduce opioid use in patients undergoing selected procedures at an ambulatory cancer surgery center. Key components of the ERAS included preoperative patient education regarding the postoperative course, liberal preoperative hydration, standardized PONV prophylaxis, appropriate intraoperative fluid management, and multimodal analgesia at all stages. METHODS: We retrospectively reviewed data on patients who underwent mastectomy with or without immediate reconstruction, minimally invasive hysterectomy, thyroidectomy, or minimally invasive prostatectomy from the opening of our institution on January 2016 to December 2018. Data collected included use of total intravenous anesthesia (TIVA), rate of PONV rescue, time to first oral opioid, and total intraoperative and postoperative opioid consumption. Compliance with ERAS elements was determined for each service. Quality outcomes included time to first ambulation, postoperative length of stay (LOS), rate of reoperation, rate of transfer to acute care hospital, 30-day readmission, and urgent care visits ≤30 days. RESULTS: We analyzed 6781 ambulatory surgery cases (2965 mastectomies, 1099 hysterectomies, 680 thyroidectomies, and 1976 prostatectomies). PONV rescue decreased most appreciably for mastectomy (28% decrease; 95% confidence interval [CI], –36 to –22). TIVA use increased for both mastectomies (28%; 95% CI, 20-40) and hysterectomies (58%; 95% CI, 46-76). Total intraoperative opioid administration decreased over time across all procedures. Time to first oral opioid decreased for all surgeries; decreases ranged from 0.96 hours (95% CI, 2.1-1.4) for thyroidectomies to 3.3 hours (95% CI, 4.5 to –1.7) for hysterectomies. Total postoperative opioid consumption did not change by a clinically meaningful degree for any surgery. Compliance with ERAS measures was generally high but varied among surgeries. CONCLUSIONS: This quality improvement study demonstrates the feasibility of implementing ERAS at an ambulatory surgery center. However, the study did not include either a concurrent or preintervention control so that further studies are needed to assess whether there is an association between implementation of ERAS components and improvements in outcomes. Nevertheless, we provide benchmarking data on postoperative outcomes during the first 3 years of ERAS implementation. Our findings reflect progressive improvement achieved through continuous feedback and education of staff.